Vegetable Waste Compost Against Growth and Production of Cucumber (Cucumis Sativus L) - Sofyan Samad; Shubzan A Mahmud; Sugeng Haryanto; Hayun Abdullah; Norman Ahmad (Green Publisher Indonesia, 2022)
Cucumber is fruit consumed by straight away. Destination how waste vegetables increase growth and production cucumber (Cucumis sativus L.). Research this is in the village South Ternate Tabona for 4 months started from month January April 2022. Ingredients and Tools. Materials used _ in study this is seed cucumber (var. hercules plus), fertilizer compost vegetables. Tool hoe, meter, scale, handsprayer, pH meter. Method study this is study experiment field with using polybag media. design random group (RAK) treatment 5 and test 3, namely: B0) without treatment, B1) 6 kg of soil + 4 kg of compost, B2) 5 kg of soil + 5 kg of compost, B3) 4 kg of soil + 6 kg of compost, B4) 3 kg of soil + 7 kg of compost. Character observation tall plant, number strand, fruit, fruit diameter, fruit length, weight fresh. Data analysis using Analysisof variance (BNT) 0.05. Results analysis variety show that growth with planting medium composition on B4 treatment (3 kg of soil + 7 kg of compost) gave enough response _ good to Cucumber, where? character 45 cm high plant, 13 strands, 3 pieces, 27 cm long fruit, 6 cm diameter fruit, and 1.37 kg weight fruit